Foreign Direct Investment, Access to Finance, and Innovation Activity in Chinese Enterprises - Girma, Sourafel; Gong, Yundan; Görg, Holger (World Bank, 2012)
A recent, comprehensive database is used to investigate the link between inward foreign direct investment (FDI) and innovation activity in China. The results of the analysis suggest that private and collectively owned firms with foreign capital participation and those with good access to domestic bank loans innovate more than other firms do. Among enterprises not owned by the state, inward FDI at the sectoral level is positively associated with domestic innovative activity only among firms that engage in their own research and development or that have good access to domestic finance. At the sector level the effect of inward FDI into technology transfer is distinguished from the effect on domestic credit opportunities. FDI affecting credit is of little significance for state-owned enterprises and is independent of their access to finance. In contrast, better access to credit is an important channel through which FDI affects the innovation of domestic private and collectively owned enterprises.